Preserving Debt Sustainability in Low-Income Countries in the Wake of the Global Crisis. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2010)
We cannot allow the return of economic stability to signify a return to "business as usual" for the IMF. The crisis exposed huge cracks in the international financial architecture of which the Fund is a key part. We have an historic responsibility to fix them. I urge all of us to recommit to seeing our collective goals to the finish line before reform fatigue sets inches.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet